Research on the impact of China’s urban rail transit on economic growth: Based on PSM-DID model - Xing-lei, Guo; Qian, Zhang; Zhen-lei, Yin; Zhong-hui, Li; Chang-zheng, Shao (Frontiers in Environmental Science, 2023)
Abstract: As a quasi-natural experiment, this paper empirically tests the effect of the opening of urban rail transit on urban economic growth based on the panel data of 286 prefecture-level cities in China from 2008 to 2020 and PSM-DID Model. This paper further analyzes the heterogeneity of cities with different population sizes and in different regions. The results reveal three conclusions. First, rail transit drives urban economic growth. Second, the promotion effect of rail transit on the economy is the largest in type II large cities, followed by type I large cities and then super-large cities, which shows heterogeneity across cities of different sizes. Third, the promotion effect of the opening of rail transit on economic growth is greater in cities in the central and western regions than in other cities, which indicates heterogeneity across cities in different regions. The findings of this study can provide a valuable reference for the government when it plans the layout of urban rail transit for construction.